EFISIENSI PENDIDIKAN BAHASA DI ERA DIGITAL: ANALISIS PENGGUNAAN ABREVIASI DALAM BERITA ILMU KOMUNIKASI TEMPO.CO - Putu Dessy Fridayanthi; Ida Ayu Agung Ekasriadi; Ni Komang Sabina Sanji Putri (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
The use of abbreviations in journalistic language is a linguistic strategy that has evolved alongside advancements in media and digital technology. In the context of online journalism, abbreviations not only serve to save space and time but also support the speed and efficiency of information delivery. This study aims to analyze the use of abbreviations in communication science news articles published on the Tempo.co website during January 2025. The research focuses on identifying the dominant types of abbreviations, their frequency, as well as their functions and purposes within the journalistic language style in digital media. This study employs a qualitative descriptive approach with content analysis methods applied to 40 news articles. Data were collected through documentation techniques involving identification and classification of abbreviation forms appearing in the news texts. The results indicate that acronyms are the most dominant type of abbreviation, found in 19 out of 23 cases (82.61%), followed by abbreviations with 4 cases (17.39%). Abbreviations were most frequently used in the Politics and Economy news categories, primarily to simplify the mention of institution names, positions, technical terms, countries, and political parties. The main function of using abbreviations is to support efficient information delivery, improve readability, and maintain clarity of meaning. Most of the abbreviations used are standardized and commonly recognized by the public. In conclusion, the use of abbreviations in Tempo.co online news reflects an adaptive effort to meet the demands of fast and concise digital communication, while reinforcing an efficient and communicative journalistic language style